2019
DOI: 10.3390/membranes9060066
|View full text |Cite
|
Sign up to set email alerts
|

Role of Operating Conditions in a Pilot Scale Investigation of Hollow Fiber Forward Osmosis Membrane Modules

Abstract: Although forward osmosis (FO) membranes have shown great promise for many applications, there are few studies attempting to create a systematization of the testing conditions at a pilot scale for FO membrane modules. To address this issue, hollow fiber forward osmosis (HFFO) membrane modules with different performances (water flux and solute rejection) have been investigated at different operating conditions. Various draw and feed flow rates, draw solute types and concentrations, transmembrane pressures, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
2
26
1
Order By: Relevance
“…One study looked at the possibility of removing foulants from coal seam gas by FO and found that the dissolved organic carbon, denosine tri-phosphate and major inorganic scalants (Ca, Mg and silica) in the coal seam gas feed were removed substantially [94]. Moreover, FO showed almost 7.5 times higher rejection of urea as compared to the RO rejections [105]. In another study [66], FO was investigated as a potential process for rejection of micropollutants; a higher rejection of bisphenol A in FO mode (99.5 ± 0.1%) than in the RO mode (97.3 ± 1.6%) were obtained.…”
Section: Specific Contaminants Removalmentioning
confidence: 99%
“…One study looked at the possibility of removing foulants from coal seam gas by FO and found that the dissolved organic carbon, denosine tri-phosphate and major inorganic scalants (Ca, Mg and silica) in the coal seam gas feed were removed substantially [94]. Moreover, FO showed almost 7.5 times higher rejection of urea as compared to the RO rejections [105]. In another study [66], FO was investigated as a potential process for rejection of micropollutants; a higher rejection of bisphenol A in FO mode (99.5 ± 0.1%) than in the RO mode (97.3 ± 1.6%) were obtained.…”
Section: Specific Contaminants Removalmentioning
confidence: 99%
“…Specific rejection studies regarding low MW organics by FO were limited. Even if, in general, rejection remains high, some compounds were poorly rejected (sometimes below 50%) under specific operating conditions (pH, membrane and draw type) especially for compounds below 100 Da (ethanol, acetic acid, urea, phenol) or some uncharged micropollutants even larger than 200 Da [ 82 , 110 , 212 , 222 , 223 , 224 ].…”
Section: Tuning Fo Process To Tackle Current Limitations For Optimmentioning
confidence: 99%
“…Very importantly, the reduction in the rejection with increasing recovery was observed, especially for compounds, such as urea, that were imperfectly rejected by FO membranes. This was expected since high recovery results in an increase in the solute concentration in the module [ 224 ]. Such observation is key for concentration process and reinforces the need for a high rejecting FO system.…”
Section: Tuning Fo Process To Tackle Current Limitations For Optimmentioning
confidence: 99%
See 2 more Smart Citations